ANALISIS PENGGUNAAN JOSUUSHI UNTUK MENGHITUNG MAKHLUK MITOLOGI PADA MINWA DITINJAU DARI SEGI SEMANTIK - Widiati, Sri Wahyu; Rahayu, Nana; ', Sulistina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: In Japanese linguistics, there is a word called josuushi or said auxiliary numbers that are used in a manner combined after numeralia principal to declare the class or set of objects, animals or humans, stated frequency or frequency, stating the size or degree, shows the shape of an object, and can also claimed the life of a person. Besides humans, animals, and objects, one other object that can be used to assess the use of josuushi are mythological creatures that can be found on minwa or folklore. This study aimed to describe josuushi used to calculate the mythological creatures in minwa and use the josuushi terms of semantics of the language units. This research is a descriptive study with data collection through library research (library research), which is looking for and collecting data from various sources related to the research. Data obtained from 14 pieces of literature which consists of 12 short stories and two novels that tell about mythological creatures and mentions josuushi used to calculate the mythological creatures. Mythological creatures contained in this study, among others, mermaids, kappa, tengu, and the dragon. Based on the analysis, it can be seen that the mermaid can use 2 forms josuushi namely nin (人) and hiki (匹), kappa only use one form josuushi only that hiki (匹), tengu can use three forms josuushi namely nin (人), hiki (匹), and wa (羽), and the dragon can use 2 forms josuushi namely hiki (匹) and tou (頭). Josuushi use to calculate the mythological creatures based on characteristics represented by each of mythological creatures that can be seen from the physical characteristic, trait or habit, environment, conditions, and so forth.Keywords: Josuushi, mythological creatures, minwa